2020
DOI: 10.1016/j.rbmo.2020.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Organoids can be established reliably from cryopreserved biopsy catheter-derived endometrial tissue of infertile women

Abstract: Organoids can be reliably established from cryopreserved endometrial tissue of infertile women and are similar to those derived from freshly biopsied tissue of the same patient. With the use of biobanked endometrial tissue, future organoid-based fertility research will no longer be limited to clinics situated near organoid laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…By exposure to a specific hormone treatment protocol encompassing E2 and progesterone (P4), organoids mimicked the full menstrual cycle as well as incipient decidualization (Table 1 and Supplementary Table 3). The robustness of the endometrial organoid platform has been validated by IHC, electron microscopy, array Comparative Genomic Hybridization (aCGH) and transcriptome analysis and, in addition, ion channel functionality and ciliogenesis was demonstrated using these organoid systems (Fitzgerald et al, 2019;Haider et al, 2019;Hennes et al, 2019;Cochrane et al, 2020;Bui et al, 2020;Luddi et al, 2020;Syed et al, 2020). Two groups achieved to derive organoids from trophoblasts, offering the appealing possibility to study trophoblast-endometrium crosstalk in vitro (Haider et al, 2018;Turco et al, 2018).…”
Section: Endometrium Healthy Endometriummentioning
confidence: 99%
“…By exposure to a specific hormone treatment protocol encompassing E2 and progesterone (P4), organoids mimicked the full menstrual cycle as well as incipient decidualization (Table 1 and Supplementary Table 3). The robustness of the endometrial organoid platform has been validated by IHC, electron microscopy, array Comparative Genomic Hybridization (aCGH) and transcriptome analysis and, in addition, ion channel functionality and ciliogenesis was demonstrated using these organoid systems (Fitzgerald et al, 2019;Haider et al, 2019;Hennes et al, 2019;Cochrane et al, 2020;Bui et al, 2020;Luddi et al, 2020;Syed et al, 2020). Two groups achieved to derive organoids from trophoblasts, offering the appealing possibility to study trophoblast-endometrium crosstalk in vitro (Haider et al, 2018;Turco et al, 2018).…”
Section: Endometrium Healthy Endometriummentioning
confidence: 99%
“…This has been demonstrated using tissue from pancreas, colon, thyroid, lung, renal and liver tumours, where tissue was frozen in cryopreservation solution and showed that organoid establishment was possible from the thawed tissue [32,111]. It has also been demonstrated that organoids established from both fresh and frozen endometrial tissue had comparable organoid formation, morphology, expression of markers, proliferation rates and response to treatment [112]. This would increase the accessibility of tissue for organoid culture and has the potential to allow many more researchers to participate in studies using these tissues.…”
Section: Cryopreservationmentioning
confidence: 92%
“…Abbreviation: EMSC, endometrial stromal cells; hESCFCs, human embryonic stem cell-derived feeder cells; SEM, standard error of the mean utilized thawed endometrial cells that were cultured for more than 3 months. Indeed, cryopreservation of freshly biopsied tissue was challenged [41]. These findings are critical for clinical application from the viewpoint that reproductive endocrinologists prepare patient-derived endometrial cells for ongoing fertility treatment in a clinical setting.…”
Section: Potential Clinical Applicationmentioning
confidence: 99%